Những câu hỏi liên quan
Tt_Cindy_tT
Xem chi tiết
Nguyễn Lê Phước Thịnh
18 tháng 6 2023 lúc 20:48

a: P(x)=6x^3-4x^2+4x-2

Q(x)=-5x^3-10x^2+6x+11

M(x)=x^3-14x^2+10x+9

b: \(C\left(x\right)=7x^4-4x^3-6x+9+3x^4-7x^3-5x^2-9x+12\)

=10x^4-11x^3-5x^2-15x+21

 

Enzo
Xem chi tiết
HT.Phong (9A5)
17 tháng 7 2023 lúc 17:37

Câu 1:

\(A\left(x\right)+B\left(x\right)\)

\(=\left(6x-4x^3+x-1\right)+\left(-3x-2x^3-5x^2+x+2\right)\)

\(=\left(6x+-3x+x\right)-\left(4x^3+2x^3\right)-5x^2+\left(-1+2\right)\)

\(=-6x^3-5x^2+4x+1\)

\(A\left(x\right)-B\left(x\right)\)

\(=\left(6x-4x^3+x-1\right)-\left(-3x-2x^3-5x^2+x+2\right)\)

\(=\left(-4x^3+2x^3\right)+5x^2+\left(6x+x-x\right)+\left(-1-2\right)\)

\(=-2x^3+5x^2+6x-3\)

Thái Nhi
Xem chi tiết
Nguyễn Lê Phước Thịnh
29 tháng 10 2023 lúc 11:56

a: \(A=x^2-4=\left(x-2\right)\left(x+2\right)\)

Khi x=102 thì \(A=\left(102-2\right)\left(102+2\right)=104\cdot100=10400\)

b: \(B=x^2+6x+9=x^2+2\cdot x\cdot3+3^2=\left(x+3\right)^2\)

Khi x=997 thì \(B=\left(997+3\right)^2=1000^2=1000000\)

c: \(C=4x^2-4xy+y^2=\left(2x\right)^2-2\cdot2x\cdot y+y^2=\left(2x-y\right)^2\)

Khi x=39 và y=-2 thì \(C=\left(2\cdot39+2\right)^2=80^2=6400\)

thuy nguyen thi
Xem chi tiết
Nguyễn Tuấn Anh Trần
Xem chi tiết
Nguyễn Lê Phước Thịnh
30 tháng 3 2022 lúc 22:13

a: \(C\left(x\right)=A\left(x\right)+B\left(x\right)\)

\(=3x^4-4x^3+5x^2-4x-3-3x^4+4x^3-5x^2+2x+6\)

=-2x+3

b: Đặt C(x)=0

=>-2x+3=0

hay x=3/2

Nguyễn Phương Anh
Xem chi tiết
Phạm Ngân
7 tháng 5 2019 lúc 9:27

x62? ko hiểu mấy a~

Kiều Trang
Xem chi tiết
Akai Haruma
30 tháng 4 2023 lúc 20:24

Yêu cầu đề bài là gì vậy bạn?

Linh Lê
Xem chi tiết
YangSu
11 tháng 4 2022 lúc 13:08

\(a,\)\(A\left(x\right)+B\left(x\right)=x^2-2x+1+x^2+2x+1=2x^2+2\)

\(b,\)\(A\left(x\right)-B\left(x\right)=x^2-2x+1-x^2-2x-1=-4x\)

\(c,\)Thay \(x=1\) vào \(A\left(x\right)\) ta được

\(A\left(x\right)=1^2-2.1+1=0\)

TV Cuber
11 tháng 4 2022 lúc 13:10

undefined

 

Nguyễn Thị Chuyên
Xem chi tiết
Nguyễn Hoàng Minh
9 tháng 9 2021 lúc 18:03

\(1,\\ a,A=4x^2\left(-3x^2+1\right)+6x^2\left(2x^2-1\right)+x^2\\ A=-12x^4+4x^2+12x^2-6x^2+x^2=-x^2=-\left(-1\right)^2=-1\\ b,B=x^2\left(-2y^3-2y^2+1\right)-2y^2\left(x^2y+x^2\right)\\ B=-2x^2y^3-2x^2y^2+x^2-2x^2y^3-2x^2y^2\\ B=-4x^2y^3-4x^2y^2+x^2\\ B=-4\left(0,5\right)^2\left(-\dfrac{1}{2}\right)^3-4\left(0,5\right)^2\left(-\dfrac{1}{2}\right)^2+\left(0,5\right)^2\\ B=\dfrac{1}{8}-\dfrac{1}{4}+\dfrac{1}{4}=\dfrac{1}{8}\)

Nguyễn Hoàng Minh
9 tháng 9 2021 lúc 18:06

\(2,\\ a,\Leftrightarrow10x-16-12x+15=12x-16+11\\ \Leftrightarrow-14x=-4\\ \Leftrightarrow x=\dfrac{2}{7}\\ b,\Leftrightarrow12x^2-4x^3+3x^3-12x^2=8\\ \Leftrightarrow-x^3=8=-2^3\\ \Leftrightarrow x=2\\ c,\Leftrightarrow4x^2\left(4x-2\right)-x^3+8x^2=15\\ \Leftrightarrow16x^3-8x^2-x^3+8x^2=15\\ \Leftrightarrow15x^3=15\\ \Leftrightarrow x^3=1\Leftrightarrow x=1\)

 

Nguyễn Hoàng Minh
9 tháng 9 2021 lúc 18:08

\(P=x\left(2x+1\right)-x^2\left(x+2\right)+x^3-x+3\\ P=2x^2+x-x^3-2x^2+x^3-x+3\\ P=3\left(đfcm\right)\)